Tree species diversity in the forest of Renikhayong para village in Bandarban, Bangladesh: a case study (Journal of Biodiversity Conservation and Bioresource Management, 2020)
The study was conducted to explore tree species diversity of Renikhayong para Village Common Forest (VCF) of Bandarban hill district. Stratified random sampling was carried out to assess the tree species diversity of the VCF. Renikhayong Para VCF with an area of 40 acres of land has more than 85 tree species belonging to 31 families, where Euphorbiaceae family was dominant containing 11 species followed by Rubiaceae (7 species), Moraceae (7 species), Meliaceae (5 species), Mimosaceae (5 species), Combretaceae (4 species), Lauraceae (4 species) and Anacardiaceae (3 species). Dominant tree species was Grewia nervosa. Renikhayong para VCF has diverse floristic resources that are known from the Shannon-Wiener’s diversity index (4.007), Simpson’s diversity index (0.028), Margalef’s richness index (13.21) and Species evenness index (0.90). However, number of species and number of individuals both were highest in the height range of 5 -